2007
DOI: 10.1111/j.1572-0241.2007.01474.x
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate Following Unsuccessful Thiopurine Therapy in Pediatric Crohn's Disease

Abstract: Methotrexate appears effective in maintaining remission in pediatric Crohn's disease, when thiopurines have failed. Consideration should be given to its use earlier in pediatric treatment algorithms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
95
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 36 publications
3
95
4
Order By: Relevance
“…Over thelastseveraldecades,therapeutic advances in the treatment of pediatric Crohn disease (CD) have included the widespread use of immunomodulators such as 6-mercaptopurine, azathioprine, and methotrexate. [1][2][3] More recently, the anti-tumor necrosis factor a (anti-TNFa) biological agents (eg, infliximab and adalimumab) have been adopted as a treatment of moderate to severe pediatric CD. 4 Although several studies on adult patients who have CD have shown a comparative benefit of anti-TNFa versus placebo 5 and thiopurines, 6 these same studies have not been done in children because of practical (time and cost) and ethical (withholding an efficacious treatment) challenges.…”
Section: Discussionmentioning
confidence: 99%
“…Over thelastseveraldecades,therapeutic advances in the treatment of pediatric Crohn disease (CD) have included the widespread use of immunomodulators such as 6-mercaptopurine, azathioprine, and methotrexate. [1][2][3] More recently, the anti-tumor necrosis factor a (anti-TNFa) biological agents (eg, infliximab and adalimumab) have been adopted as a treatment of moderate to severe pediatric CD. 4 Although several studies on adult patients who have CD have shown a comparative benefit of anti-TNFa versus placebo 5 and thiopurines, 6 these same studies have not been done in children because of practical (time and cost) and ethical (withholding an efficacious treatment) challenges.…”
Section: Discussionmentioning
confidence: 99%
“…4 It has remained a topic of great debate whether childhood-onset disease is etiologically distinct from adultonset disease-a debate recently catalyzed by the search for susceptibility genes in CD and UC. Clinical experience, including the early requirement for second-line immunomodulatory drugs 5,6 in childhood-onset disease, suggests that childhood-onset disease may have a more "severe" phenotype. This hypothesis has been supported to some extent by the limited available data suggesting that childhood-onset CD may be characterized by extensive intestinal involvement at presentation.…”
mentioning
confidence: 99%
“…42 . As yet, there is no mechanism proposed at to potential pathways which may explain this improvement in growth for either AZA or MTX.…”
Section: Discussionmentioning
confidence: 99%